Synthetic fatty acid from crude oil of Tamsagbulag petroleum deposit (Mongolia) - Bayanmunkh, Myagmargerel; Bayasgalan, Khulan; Byambasuren, Gantsetseg; Batchuluun, Khongorzul; Murneren, Tuya (Mongolian Journal of Chemistry, 2021)
In this work, we studied to obtain synthetic fatty acids raw materials to produce surfactants and various detergents from paraffin. The solid paraffin extracted from the Tamsagbulag petroleum deposit was 46 mass%, distilled 350-450°C, by complexing with urea. Experimental study indicates paraffin's physicochemical characteristics from this petroleum are more suitable to use in the production of synthetic fatty acids. By solid paraffin oxidation, we obtained 33.01% of the synthetic fatty acids containing monocarboxylic acids. We suggest obtaining the synthetic fatty acid by oxidation process in normal condition from petroleum paraffin.